Highly Stable Co Single Atom Confined in Hierarchical Carbon Molecular Sieve as Efficient Electrocatalysts in Metal–Air Batteries - Liang, Shuang; Zou, Lian‐Chun; Zheng, Li‐Jun; Li, Fei; Wang, Xiao‐Xue; Song, Li‐Na; Xu, Ji‐Jing (Advanced energy materials, 2022)
Single atoms catalysts’ (SACs) applications in the energy storage field are hindered by their insufficient stability and poor recyclability due to their oxidation and agglomeration. To address this challenge, herein, a Co‐CMS composite material is synthesized by confining Co SACs into the highly ordered pores of the carbon molecular sieve (CMS). Related theoretical and experimental methods prove that the microporous trapping and hydroxyl doping of CMS are favorable for synergistically stabilizing the precursor and contributing to the subsequent conversion of single atoms with strong interactions between Co, O, and N. The unique 3D spiral pore structure of CMS facilitates the mass transfer of reactants and the highly dispersed Co single atoms confined in CMS increase the active sites. These properties are ideal for oxygen reduction reaction catalysts. Benefiting from the above‐mentioned superiority, the Co‐CMS cathode exhibits superior performance in a rechargeable Zn–air battery with a lower charge–discharge voltage gap of 0.77 V and a power density of 219 mW cm−2. The applications of Co‐CMS catalysts are also extended to other metal–air batteries in this work, which further highlights the advantages of carbon molecular sieves in stabilizing SACs materials. A new strategy for using the confinement effect of hierarchical carbon molecular sieves (CMS) to stabilize single atoms is deeply studied. This strategy enables the fabrication of a satisfactory oxygen reduction reaction catalyst. The synergistic effect of the micropore capture effect and the hydroxyl group of CMS produce excellent results. The Co‐CMS catalyst displays promising applications in the field of metal–air batteries.